A comparison of cabbage leaves vs . hot and cold compresses in the treatment of breast engorgement - Arora Smriti; Vatsa Manju; Dadhwal Vatsla (Wolters Kluwer Medknow Publications, 2008)
Objective: To assess and compare the efficacy of cold cabbage leaves and hot and cold compresses in the treatment of breast engorgement. Material and Methods: This was a quasi-experimental study conducted in the postnatal ward of the All India Institute of Medical Sciences (AIIMS), New Delhi. The study comprised a total of 60 mothers; 30 in the experimental group and 30 in the control group. The control group received alternate hot and cold compresses and the experimental group received cold cabbage leaf treatment for relieving breast engorgement. The pre- and posttreatment scores of breast engorgement and pain were recorded. The data were analyzed using descriptive and inferential statistical methods using the statistical software STRATA. Results: Both the treatments, i.e., hot and cold compress and cabbage leaves were effective in decreasing breast engorgement and pain in postnatal mothers ( P ≤ 0.001). Cold cabbage leaves and hot and cold compress were both equally effective in decreasing breast engorgement ( P = 0.07), whereas hot and cold compresses were found to be more effective than cold cabbage leaves in relieving pain due to breast engorgement ( P ≤ 0.001) in postnatal mothers. Conclusion: Cold cabbage leaves as well as alternate hot and cold compresses both can be used in the treatment of breast engorgement. Hot and cold compresses are more effective in decreasing pain than cold cabbage leaves in relieving pan due to breast engorgement.